ANALISIS PENETAPAN PENGADILAN AGAMA LAMONGAN NO: 70/PDT.P/PA.LMG. TENTANG DISPENSASI KAWIN - M. Zainuddin Alanshori (Universitas Islam Lamongan, 2017)
This study aims to answer the questions of what is the consideration of judges in the Lamongan Religious Court on the establishment of marriage dispensation on the grounds of being able to give so-called nafkah (feed) and what is the perspective of Islamic Law and Marriage Law in Indonesia against the establishment of Lamongan Religious Court judges about marriage dispensation on the grounds to be able to give nafkah. In order to answer the above questions, the writer used data collection techniques through documentation and interviews by using descriptive analysis with deductive mindset. The study concludes that the judge stipulating the dispensation of marriage on the grounds of being able to give nafkah is based on the fulfillment of the conditions of marriage except the age requirement for the prospective grooms having not reached the age of 19 years, as meant in the Compilation of Islamic Law Article 15 paragraph 1: (1)